2017
DOI: 10.1177/1040638717710451
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validation of a reference laboratory ELISA for the detection of feline leukemia virus p27 antigen

Abstract: Feline leukemia virus (FeLV) is an oncogenic retrovirus of cats. Immunoassays for the p27 core protein of FeLV aid in the detection of FeLV infections. Commercial microtiter-plate ELISAs have rapid protocols and visual result interpretation, limiting their usefulness in high-throughput situations. The purpose of our study was to validate the PetChek FeLV 15 ELISA, which is designed for the reference laboratory, and incorporates sequential, orthogonal screening and confirmatory protocols. A cutoff for the scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The manufacturer reports this test has a sensitivity of ≥94.9% and a specificity of ≥98.4% defined by combined results of other p27 antigen test brands and virus isolation. PetChek ® FeLV 15 ELISA was performed with sequential screening and confirmatory protocols, including a neutralization step to reduce nonspecific reactivity as described . The sensitivity and specificity of this modified assay were both reported to be 100% defined by the combined results of FeLV PCR and ViraCHEK ® /FeLV .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer reports this test has a sensitivity of ≥94.9% and a specificity of ≥98.4% defined by combined results of other p27 antigen test brands and virus isolation. PetChek ® FeLV 15 ELISA was performed with sequential screening and confirmatory protocols, including a neutralization step to reduce nonspecific reactivity as described . The sensitivity and specificity of this modified assay were both reported to be 100% defined by the combined results of FeLV PCR and ViraCHEK ® /FeLV .…”
Section: Methodsmentioning
confidence: 99%
“…PetChek ® FeLV 15 ELISA was performed with sequential screening and confirmatory protocols, including a neutralization step to reduce nonspecific reactivity as described . The sensitivity and specificity of this modified assay were both reported to be 100% defined by the combined results of FeLV PCR and ViraCHEK ® /FeLV . A total of 10 samples were discarded because they were positive on PetChek ® and negative on ViraCHEK ® .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, inclinic diagnosis of FeLV infection relies on antigen testing rather than antibody testing. 7,8,16,21,[40][41][42] FeLV PCR testing is not without its limitations, with false-positives caused by DNA contamination during PCR set up and falsenegatives caused by mutations in the targeted region of the virus being possible. Evaluation of FeLV PoC test kit performance is challenging because of the absence of a clearly defined 'gold standard' for diagnosing FeLV infection.…”
Section: Felv Diagnosis Using Whole Blood and Poc Antigen Test Kitsmentioning
confidence: 99%
“…14,39 For more detail about other diagnostic methods of FeLV detection, including virus isolation, immunofluorescence for detection of FeLV cell-associated p27 antigen in circulating leukocytes and platelets, and most recently a laboratory-based ELISA to detect p27 antigen (PetChek FeLV 15™), we refer to studies published elsewhere. 7,8,16,21,[40][41][42] FeLV PCR testing is not without its limitations, with false-positives caused by DNA contamination during PCR set up and falsenegatives caused by mutations in the targeted region of the virus being possible. However, one important advantage of PCR testing over all other currently available diagnostic methodologies is its ability to detect regressive FeLV infections.…”
Section: Felv Diagnosis Using Whole Blood and Poc Antigen Test Kitsmentioning
confidence: 99%
“…The core protein of FeLV, p27, is a soluble antigen that is produced in great excess which makes it ideal for detection by immunoassays. Several of the immunoassays that detect p27 antigen in cats employ a pair of high affinity, monoclonal antibodies that, when optimized in an enzyme-linked immunosorbent assay (ELISA), can be very sensitive and specific [22][23][24]. Studies in both experimentally infected and naturally infected cats have demonstrated a strong association between the copy numbers of proviral DNA and p27 antigen level in the circulation and clinical course of infection [5,25].…”
Section: Introductionmentioning
confidence: 99%